Effectiveness and tolerability of Poliprotect, a natural mucosal protective agent for gastroesophageal reflux disease and dyspepsia: Surveys from patients, physicians, and pharmacists - Cioeta, Roberto; Muti, Paola; Rigoni, Marta; Morlando, Luigi; Siragusa, Filippo; Cossu, Andrea; Giovagnoni, Emiliano (Frontiers in Drug Safety and Regulation, 2022)
Background: Gastroesophageal reflux disease (GERD), and functional dyspepsia (FD) are very common in the general population. GERD prevalence is considerably high in pregnant women, and it is increasing at young age, alongside with obesity. Mucosal protective agents (MPA) are over the counter (OTC) treatments for FD and GERD commonly used alone or as add-on therapy to proton pump inhibitors (PPIs). Real World data through surveys allow a clinical evaluation of marketed products, that complies also with the new regulation on substance-based medical devices (SBMD). Aim: to evaluate a natural MPA perceived effectiveness, safety and pattern of usage among patients, physician, and pharmacists, as assessed by a validated survey methodology Methods: Questionnaire repeatability was first assessed, resulting in intraclass correlation coefficient agreement level >0.9 in the 3 validation cohorts. All questions were closed multiple choice questions, allowing measuring variations in frequency, quality or magnitude of effect on a 5-point Likert-like verbal scale. Results: Three different surveys were performed in Italy and Spain on a total of 3,471 physicians, including 77 gastroenterologists, 848 patients and 146 pharmacists who had experience of the MPA in the previous year. Over 90% of general practitioners (GPs) answers rated MPA effectiveness as good/excellent in controlling pyrosis, 80% for epigastric pain, and approximately 70% in digestion difficulties. GPs reported MPA as very or extremely useful as an alternative to PPIs (73%) and for pregnancy-associated GERD symptoms (61%), almost unanimously (99.5%) reporting an excellent to good tolerability; 79% of the gastroenterologists answered to be extremely or very satisfied with the improvement of typical GERD symptoms, whereas improvement of dyspepsia, pregnancy- and breast-feeding associated GERD symptoms was rated as highly satisfactory for 69%, 52% and 62%, respectively among GI specialists. Use because of painful dyspeptic symptoms was reported by over 80% of patients, who rated symptom relief as excellent/good, and reported a marked quality-of-life improvement in 73% and in 65% of their answers, respectively. Conclusions: Large-scale, validated surveys support safety and effectiveness of the natural MPA in the treatment of frequent functional upper GI disorders.